How to make anyone fall in love with you - Lowndes, Leil. ([Roseland, N.J.] : Listen & Live Audio, 1997)
From bestselling author Leil Lowndes comes the surefire guide to love for anyone seeking romantic bliss. In "How to make anyone fall in love with you", listeners will find dozens of techniques, based on scientific studies, regarding the nature of love, including: Finding potential love partners. Making an unforgettable first impression. Dodging "love bloopers." Establishing sexual rapport. By using these pragmatic, down-to-earth strategies, anyone can turn a new or casual relationship into a lasting one--or make current relationships deeper.
Keywords: Intimacy (Psychology); Love; Man-woman relationships; Sexual excitement; Overdrive